Describing and expanding the clinical phenotype of anti-MDA5-associated rapidly progressive interstitial lung disease: case series of nine Canadian patients and literature review. (4th May 2018) - Hoa, S; Troyanov, Y; Fritzler, MJ; Targoff, IN; Chartrand, S; Mansour, AM; Rich, E; Boudabbouz, H; Bourré-Tessier, J; Albert, M; Goulet, JR; Landry, M; et al.
Abstract : Objective : To describe and expand the phenotype of anti-MDA5-associated rapidly progressive interstitial lung disease (MDA5-RPILD) in Canadian patients. Method : All proven cases of MDA5-RPILD hospitalized in the University of Montreal's affiliated centres from 2004 to 2015 were selected for inclusion. Results : Of nine consecutive patients, RPILD was the presenting manifestation in seven, whereas two patients developed RPILD 2 years after the onset of arthritis and of chronic interstitial lung disease. In the case with arthritis, RPILD was probably triggered by initiation of tumour necrosis factor-α-inhibitor therapy. In most patients (89%), RPILD was accompanied by concomitant onset of palmar/lateral finger papules, skin ulcerations, and/or mechanic's hands. All patients experienced profound weight loss over 1–2 months (mean ± SD 10.2 ± 4.8 kg). All had arthralgias and/or arthritis. Six patients were clinically amyopathic; only one patient had creatine kinase (CK) levels > 500 U/L. Initial ferritin and transaminase levels were elevated in 86% and 67% of patients, respectively. The antinuclear antibody (ANA) test was negative for nuclear and cytoplasmic staining; antisynthetase autoantibodies were negative. Three patients died; time from initial symptoms to death ranged from 7 to 15 weeks. All six survivors received mycophenolate mofetil and/or tacrolimus as part of induction and/or maintenance therapy. Conclusion : In an inpatient setting, RPILD associated with characteristic skin rashes, profound weight loss, articular symptoms, normal or low CK with elevated ferritin, and absent fluorescence on ANA testing should alert the clinician to the possibility of MDA5-RPILD. T-cell-mediated therapies may play a role in this highly lethal condition.